Kinerja Aparat Dalam Pelayanan Administrasi Kependudukan Pada Masyarakat di Kantor Camat Pasir Putih Kabupaten Muna - R, Risman; Sulila, Ismet; Abdussamad, Juriko (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Research on the Performance of Officials in Administrative Services at the Pasir Putih Subdistrict Office, with problems including the knowledge and motivation of officials in carrying out services to the community. Apart from that, this research also aims to describe the knowledge and motivation of officers in carrying out services. To be able to answer this research problem, this research uses a qualitative research method with a phenomological approach. This needs to be done to understand and know clearly the information that is the main variable in this research. From the results of data analysis, it was found that 1) In principle, the service runs as usual, where every person who is the party being served, both administratively and in connection with consultation, can be served. However, the service process does not meet expectations such as speed and responsiveness and one of the causes is the lack of facilities and relatively low employee attendance. 2) Furthermore, the knowledge possessed by officers who work in the office does not require formal education because it has no impact on existing work, because the principles of service work are more routine oriented, and there are no types of work that are innovative and require special knowledge. Usually there are policies that are implementable from the government/region, sub-districts as technical implementers accompanied by complete technical guidelines. 3) Regarding the motivation of officers working at the Pasir Putih Subdistrict Office, from the results of data analysis, it was found that a person's ability to carry out work can be seen from his enthusiasm, but motivation can also be seen from the impact of carrying out work on self-development achievements which is relatively lacking or even non-existent. Motivation is seen only due to encouragement from an officer because of ASN status and efforts to avoid obstacles in the regular promotion process.